(untitled) (Scientia Agricola, 2015)
The sombric horizon is a diagnostic subsurface horizon defined in the soil classification system of the United States (Soil Taxonomy) and FAO (WRB), used to classify the soil at different categorical levels. The sombric horizon has a soil color darker than the overlying surface(s) horizon(s), and must show illuvial humus accumulation features, though they are not associated with aluminum (Al), as in the spodic horizon, nor associated with sodium (Na), as in the natric horizon. There are also criteria to distinguish it from buried A horizons. However, since the first references and proposed concept of the sombric horizon in African soils made by Sys and co-workers in the 1960s, and adopted by the Soil Taxonomy edition of 1975, few modifications have been made to its definition. Moreover, the pedogenic process involved in illuvial humus accumulation in these horizons remains inadequately clarified, making the distinction between the sombric and spodic or buried A horizon difficult and unclear. This review reports the historical evolution of the sombric horizon concept, its definition and inconsistencies under different soil classification systems, and the current hypothesis, together with its fragilities, proposed to explain the soil illuvial humus accumulation. Although it is recognized that further research is necessary, alternative criteria are proposed for the definition of the sombric horizon in the Brazilian System of Soil Classification.